Fuzzy logic-based intelligent irrigation system with mobile application - Azry, Anis S; Derahman, Md N; Mohamad, Zarina; Rahiman, Amir R. A.; A. Muzakkari, Bashir; Mohamed, Mohamad A. (Little Lion Scientific, 2022)
Current irrigation scheduling is inefficient and inaccurate as it still relies heavily on human labour which can lead to over- or under-irrigation, affecting crop quality and workers productivity. This study proposes an implementation of an Internet-of-Things (IoT)-based irrigation system with fuzzy logic to improve the efficiency of the irrigation process. That includes the development of a mobile application called Chill-I, which acts as a remote reporter for the agricultural contractor. In addition, this system was developed specifically for the bird's eye chilli crop, which is grown on a large scale. With three inputs, soil moisture, humidity and temperature collected by the sensors, the system uses fuzzy logic processing capability to generate the output of water pumping at different rate. The results showed that fuzzy logic-based system increases the efficiency of automatic irrigation, rather than setting a fixed water pumping rate for the plant or only the ON/OFF option. Moreover, the mobile application allows remote monitoring of plants reducing unnecessary resources and improve intervention efficiency when needed.